Investigation of the Interaction of Palladium with Potassium Tetrafluorobromate; Journal of Physics: Conference Series; Vol. 1443 : Issues of Physics and Technology in Science, Power Industry and Medicine" (IPTSPIM-2019) - Mamatova A. M. Alina Manasovna; Shakimova A. M.; Merkel K. I.; Malin A. V. Artem Vladimirovich; Ostvald R. V. Roman Vyacheslavovich (2020, 2020)
Title screen